Revisiting Tools for Change: Reflections on Methodologies and Desire-based Approaches in Roma-related Research - Lindroos, Sanni (Central European University, 2026)
In this article, I revisit some of the main critiques, questions and suggestions in relation to methodological approaches emergingalongside the discipline of Critical Romani Studies. Drawing from Indigenous Studies scholar Eve Tuck’s notion of desire-basedresearch, I apply the three goals that Tuck set to foster emancipatory methodologies as a framework to reflect on the strengths andlimitations of previously proposed methodologies in Romanirelated research. By establishing counterhistories of Roma, Romanischolarship, a reconfiguration of the archive, and reflections on critical whiteness as the main topics in the epistemological paradigmshift unfolding over the past decade, I suggest some further points for methodological consideration that could advance the discipline.In particular, I discuss the possibility of co-researching as a mode of participatory knowledge production and propose digital platforms as a potential site of research, as well as call for further reflections on how to make research results more accessible to wider audiences.